Estudo da eficiência de reforços estruturais em vigas de concreto armado com o uso de chapas de aço coladas com resina epóxi: uma análise qualitativa - Luizon, João Victor Neves [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
In civil engineering, a structure is the whole sustainment of a construction and, thus, it is important that it remains intact throughout its lifetime. An engineering construction must last for decades without losing its functionality. However its purpose may be altered and several times the original structure does not meet the new needs of use. Still, in new buildings, the functionality is altered due to possible flaws in execution and the structure, invariably does not reach the desired solicitation needs. In cases like this, the commonly adopted solutions are, basically, the demolishment followed by the reconstruction of the desired mold or the structural reinforcement. This second option, for long years, has not been put to practice due to certain factors such as the high costs for its implantation, use of inadequate reinforcement execution techniques, and the culture of people involved in the area regarding its use and, in this case, the option would always be the reconstruction. Thoughtout the years, some techniques were developed to allow the execution of structural reinforcements with low costs and in efficient ways. An interesting, fast, efficient and economical technique is the structural reinforcement through metal sheets put together with epoxy resin that can be applied in beams, slabs and pillars. In the present work the different behavior of beams reinforced with this technique. Steel is a very recommended material for these reinforcements due to its characteristics related to traction, compression and the effectiveness of the technique related to its cost. For the attachment the epoxy resin is recommended, since it allows the joining of two materials, in this case, steel and concrete. The efficiency of this union is so considerably high that it rarely produces any flaws in adherence and, normally, when it happens it is due to problems in the execution process, not in the union of materials

Na engenharia civil uma estrutura é a sustentação de toda obra e, portanto, é importante que se mantenha intacta por toda a vida útil. Uma obra de engenharia civil deve durar décadas sem perder sua funcionalidade. Entretanto a finalidade pode ser alterada e muitas vezes a estrutura inicial passa a não atender a necessidade da nova utilização. Ainda, em novas construções a funcionalidade é alterada divido a possíveis falhas na execução e a estrutura invariavelmente não atinge as necessidades de solicitação desejada. Em casos como esses as soluções geralmente adotadas são, basicamente, a demolição seguida da reconstrução dos moldes desejados ou então o reforço estrutural. Esta segunda opção por muitos anos não foi aplicada devido a certos fatores como o alto custo de implantação, utilização de técnicas inadequadas de execução do reforço e a cultura do próprio meio quanto a sua utilização e, neste caso, a opção recaia na reconstrução. Ao longo dos anos algumas técnicas foram desenvolvidas para se executar reforços estruturais com baixo custo e de forma eficiente. Uma técnica interessante, rápida, eficaz e econômica é o reforço estrutural através de chapas metálicas coladas com resina epóxi que pode ser aplicada em vigas, lajes e pilares. No presente trabalho é estudado o diferente comportamento de vigas reforçadas utilizando esta técnica. O aço é um material bastante recomendado para os reforços devido às suas características quanto à resistência a tração, compressão e a eficiência da técnica em relação a seu custo. Para a colagem recomenda-se o uso de resina epóxi, pois permite a união dos materiais, no caso o aço e o concreto. A eficiência desta união é consideravelmente elevada que raramente se produz alguma falha de aderência e normalmente quando ocorre é devido a problemas na execução e não na união dos materiais
Keywords: Engenharia de estruturas; Aço - Estruturas; Vigas; Estabilidade estrutural; Structural reinforcement